lncRNA KCNQ1OT1 Suppresses the Inflammation and Proliferation of Vascular Smooth Muscle Cells through IκBa in Intimal Hyperplasia - Bozhi Ye; Zi-heng Wu; Tung Yu Tsui; Bao-fu Zhang; Xiang Su; Yi-hui Qiu; Xiang-tao Zheng (Elsevier, 2020)
Inflammation and proliferation of vascular smooth muscle cells (VSMCs) are the key events in intimal hyperplasia. This study aimed to explore the mechanism by which long non-coding RNA (lncRNA) KCNQ1OT1 affects VSMC inflammation and proliferation in this context. A vein graft (VG) model was established in mice to introduce intimal hyperplasia. Isolated normal VSMCs were induced with platelet-derived growth factor type BB (PDGF-BB), and the cell proliferation, migration, and secretion of inflammatory factors were determined. The results showed that KCNQ1OT1 was downregulated in the VSMCs from mice with intimal hyperplasia and in the PDGF-BB-treated VSMCs, and such downregulation of KCNQ1OT1 resulted from the increased methylation level in the KCNQ1OT1 promoter. Overexpressing KCNQ1OT1 suppressed PDFG-BB-induced VSMC proliferation, migration, and secretion of inflammatory factors. In VSMCs, KCNQ1OT1 bound to the nuclear transcription factor kappa Ba (IκBa) protein and increased the cellular IκBa level by reducing phosphorylation and promoting ubiquitination of the IκBa protein. Meanwhile, KCNQ1OT1 promoted the expression of IκBa by sponging miR-221. The effects of KCNQ1OT1 knockdown on promoting VSMC proliferation, migration, and secretion of inflammatory factors were abolished by IκBa overexpression. The roles of KCNQ1OT1 in reducing the intimal area and inhibiting IκBa expression were proved in the VG mouse model after KCNQ1OT1 overexpression. In conclusion, KCNQ1OT1 attenuated intimal hyperplasia by suppressing the inflammation and proliferation of VSMCs, in which the mechanism upregulated IκBa expression by binding to the IκBa protein and sponging miR-221.